Programming a Pneumatic Processes Sequence based on PLC by Demonstration - Al-Mesaody, Amer (Al-Khwarizmi Engineering Journal, 2017)
Abstract Pneumatic processes sequence (PPS) is used widely in industrial applications. It is common to do a predetermined PPS to achieve a specific larger task within the industrial application like the PPS achieved by the pick and place industrial robot arm. This sequence may require change depending on changing the required task and usually this requires the programmer intervention to change the sequence’ sprogram, which is costly and may take long time. In this research a PLC-based PPS control system is designed and implemented, in which the PPS is programmed by demonstration. The PPS could be changed by demonstrating the new required sequence via the user by following simple series of manual steps without having to change the PLC’s original program, which leads to decreasing the cost and time. Keywords: FIFO function block, Programming by Demonstration (PbD), System Frame.